Stray warmings : Nina Canell ; [on the occasions of Nina Canell's Exhibition Stray Warmings, February 15 - April 6, 2013, at Midway Contemporary Art] - Smith, Leslie; Connor, Steven; Roelstraete, Dieter; Szewczyk, Monika; Canell, Nina (Sternberg Press, 2014)
Testing the intimate intersection of audience, object, and event, Nina Canells work has been described by curator Fionn Meade as tethered to fragmented and often partially withheld narratives [and] comprised of choreographed indirection and relay. Published in relation to the exhibition Stray Warmings at Midway Contemporary Art in Minneapolis, this new monograph brings together writing and reproductions that extend beyond this particular context. The book documents the broader framework that has defined the artists practice during the past years, considering how intuition, corners, and a stratification of the transparent have formed Canells understanding of sculpture and its dissolution.